Depressive Symptoms and Achievement Goals: Parental Rejection as a Moderator. (November 2020) - Măirean, Cornelia; Diaconu-Gherasim, Loredana R.
This present study investigated the longitudinal relations between depressive symptoms and achievement goals and whether maternal and paternal rejection moderated these relations. A sample of 436 early adolescents (X ¯ age = 13.19, 58.33% girls) filled in scales measuring the depressive symptoms (Time 1), parental rejection (Time 2; 1 year later), and achievement goals (Time 2). Early adolescents' depressive symptoms were positively related to performance-avoidance goals and negatively related to mastery and performance-approach goals. Furthermore, the father's rejection was positively related to the adolescents' performance-avoidance and negatively related to mastery goals, whereas maternal rejection was not related to achievement goals. Finally, maternal rejection moderated the association between depressive symptoms and performance-avoidance goals 1 year later. The implications of these results for future studies and educational practices are discussed.